2010
DOI: 10.1074/jbc.m109.075143
|View full text |Cite
|
Sign up to set email alerts
|

The TOR Complex 1 Is Distributed in Endosomes and in Retrograde Vesicles That Form from the Vacuole Membrane and Plays an Important Role in the Vacuole Import and Degradation Pathway

Abstract: The key gluconeogenic enzyme fructose-1,6-bisphosphatase (FBPase) is induced when Saccharomyces cerevisiae are starved of glucose. However, when glucose is added to cells that have been starved for 3 days, FBPase is degraded in the vacuole. FBPase is first imported to Vid (vacuole import and degradation) vesicles, and these vesicles then merge with the endocytic pathway. In this report we show that two additional gluconeogenic enzymes, isocitrate lyase and phosphoenolpyruvate carboxykinase, were also degraded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…In contrast, when glucose was added to cells that were starved for 3 d, FBPase degradation was impaired. This indicates that while vacuole proteinases are not essential for FBPase degradation in 1 d starved cells, they are essential for cells starved for 3 d. More significantly, our lab has recently demonstrated that other gluconeogenesis enzymes such as MDH2, Pck1p and Icl1p also share the same degradation characteristics as FBPase [29,30] .…”
Section: Degradation Of Gluconeogenic Enzymesmentioning
confidence: 91%
See 3 more Smart Citations
“…In contrast, when glucose was added to cells that were starved for 3 d, FBPase degradation was impaired. This indicates that while vacuole proteinases are not essential for FBPase degradation in 1 d starved cells, they are essential for cells starved for 3 d. More significantly, our lab has recently demonstrated that other gluconeogenesis enzymes such as MDH2, Pck1p and Icl1p also share the same degradation characteristics as FBPase [29,30] .…”
Section: Degradation Of Gluconeogenic Enzymesmentioning
confidence: 91%
“…The bound material was subjected to MALDI analysis. This facilitated in identifying Tco89p among other cellular protein candidates [30] . Tco89p is a component of the TORC1 which is also comprised of Tor1p, Kog1p and Lst8p [53,54] .…”
Section: The Tor Complex 1 Interacts With Multiple Cargo Proteins Tarmentioning
confidence: 99%
See 2 more Smart Citations
“…The two primary mechanisms for subcellular degradation are the ubiquitin-proteasome system (UPS) and autophagy. A third, less-well-characterized, mechanism is the vacuole import and degradation (Vid) pathway (Hoffman and Chiang 1996), for which the most critical substrate is fructose-1,6-bisphosphatase (Fbp1), the key enzyme in gluconeogenesis, but other target proteins include Pck1, Mdh2, and Icl1 (Hung et al 2004;Brown et al 2010). Degradation of Fbp1 in the absence of glucose prevents futile cycling where the cell attempts to generate glucose under conditions where the carbon source is limiting.…”
mentioning
confidence: 99%